Genomic Epidemiology of bla-KPC Klebsiella pneumoniae (KPC-Kp) in a High-Transmission Long-Term Acute Care Hospital (LTACH). (4th October 2017) - Hawken, Shawn E; Lolans, Karen; Lin, Michael Y; Hayden, Mary K; Snitkin, Evan S; ,
Abstract: Background: High prevalence of multidrug-resistant organisms (MDROs) and low resolution of traditional molecular epidemiologic methods hinder efforts to delineate nosocomial transmission pathways. We hypothesize that whole-genome sequencing (WGS) can overcome these obstacles if sample collections, meta-data and analytical strategies are tailored to answer specific epidemiologic questions. Methods: Our objective was to apply genomics to identify pathways of KPC-Kp transmission linked to imported cases in an LTACH. We performed WGS on KPC-Kp isolates derived from admission and every-14-day surveillance culturing of 259 patients from an LTACH in Chicago, IL over one year (sampling adherence, 94%). We leveraged WGS and admission surveillance data to develop and apply a phylogenetic approach to identify transmission clusters linked to imported cases. Clusters were analyzed in the context of patient locations to determine routes of transmission. Results: We identified 28 transmission clusters of patient acquisitions (median 1, range1–11, SD 2) traced back to each imported case. Clusters showed a range of genetic diversity (Figure 1), arguing against relying on a fixed variant threshold to define transmission. While 82% of acquisitions could be explained by overlap in the LTACH with an imported case in the same cluster, only 54% were explained by floor overlap (Figure 2). Analysis of 14-day windows preceding acquisitions revealed an association between cluster size and patient movement; cluster size was positively correlated with both the number of floors where acquisitions occurred and the number of inter-floor movements by patients who acquired KPC-Kp (Spearman correlation, R = 0.79, P <.001 and R = 0.44 P < .02). Conclusion: Phylogenetically defined KPC-Kp transmission clusters in an LTACH ranged in size and genetic diversity. Despite sequencing isolates derived from near complete surveillance of patients, a source patient on the same floor could not be identified in 46% of transmissions, suggesting an unidentified environmental, common location, or inter-floor healthcare worker source. Patient movement between floors was associated with cluster size, indicating intra-facility movement may increase transmission risk. Disclosures: M. K. Hayden, OpGen, Inc.: Receipt of donated laboratory services for project, Research support. Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product and Research grant. Molnlycke: Grant Investigator and Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product. Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product.